Atypical Manifestation of DRESS Syndrome. (13th April 2020) - Hakim, Christopher; Melitas, Constantine; Nguyen, Eric; Ngo, Kha
Abstract : The differential for liver transaminases over 1000 units/liter typically includes liver ischemia, acute viral hepatitis, acetaminophen toxicity, and autoimmune hepatitis. Prompt evaluation is imperative as these etiologies can lead to fulminant liver failure. We present a case of transaminases over 1000 units/liter from an atypical etiology. A 52-year-old male, previously treated with allopurinol for an acute gout flare, presented with persistent fevers. Given that he had taken a "high-risk medication" 2–6 weeks before presentation, subsequently presented with fever, rash, renal impairment, elevated liver enzymes in the thousands, and peripheral eosinophilia, DRESS syndrome secondary to allopurinol was diagnosed.